Clustering of European SMEs According to Their Financial Behaviour - Ádám Balog; Benedek Lits (Köz-gazdaság)
This study carries out a holistic cluster analysis of the financing structure of 13 103 SMEs in 27 EU Member States, Iceland, Liechtenstein, and Norway, and 9 343 SMEs in the euro area Member States countries based on a dataset provided by the European Central Bank from the Survey on the Access to Finance of Enterprises (SAFE) in the 27th and 28th rounds, respectively. The study approaches the topic through a 2015 EIF research while developing it further in several manners. It defines five distinct types of financing: Self-financed SMEs, Credit-financed and subsidised SMEs, Flexibly financed SMEs, Supplier-financed SMEs and Lease-financed SMEs. Our results revealed different patterns and attitudes towards financing, based on variables such as country, sector, and size, which may support policymakers in finding appropriate measures to deal with the various types of SMEs.